2016
DOI: 10.3389/fphys.2015.00372
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Different Environmental Conditions on Cognitive Function: A Focused Review

Abstract: Cognitive function defines performance in objective tasks that require conscious mental effort. Extreme environments, namely heat, hypoxia, and cold can all alter human cognitive function due to a variety of psychological and/or biological processes. The aims of this Focused Review were to discuss; (1) the current state of knowledge on the effects of heat, hypoxic and cold stress on cognitive function, (2) the potential mechanisms underpinning these alterations, and (3) plausible interventions that may maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
209
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 233 publications
(216 citation statements)
references
References 105 publications
4
209
1
2
Order By: Relevance
“…Although the present study did not measure temperature, other studies have shown that wearing PPC increases core temperature, increases sweating, and leads to dehydration . A recent review reported that heat stress could decrease performance during “complex” cognitive tasks, such as executive functions . Consequently, the increase in core temperature with the PPC might also have had a negative impact on the participants’ cognitive functions.…”
Section: Discussionmentioning
confidence: 70%
“…Although the present study did not measure temperature, other studies have shown that wearing PPC increases core temperature, increases sweating, and leads to dehydration . A recent review reported that heat stress could decrease performance during “complex” cognitive tasks, such as executive functions . Consequently, the increase in core temperature with the PPC might also have had a negative impact on the participants’ cognitive functions.…”
Section: Discussionmentioning
confidence: 70%
“…Therefore, it is not surprising to observe no performance degradation in short-term memory during heat exposure in both groups, although Johnson et al [9] and Wright et al [10] suggested that small changes in body temperature may have influence on human performance. However, a recent review by Taylor et al [34] suggests that core temperature alone may not be a reliable predictor of cognitive performance decline in hot environment. The task difficulty level could be the factor affecting cognitive function [13, 29].…”
Section: Discussionmentioning
confidence: 99%
“…Second, increase of core temperature alone might not be a reliable predictor of performance deterioration [34]. Japanese subjects reported more negative feelings during heat exposure condition than tropical subjects; they felt the condition was hotter and more thermally discomfort than tropical subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, altitude (Yan, 2014), hypoxia, heat and cold stress, known to be both task- and severity-dependent, are probably linked to the cognitive and sensory status of an athlete (Ruffini et al, 2015; Taylor et al, 2016) and are experienced by RandoRaid and ultra-trail athletes competing in a race like the Transpyrénéa.…”
Section: Discussionmentioning
confidence: 99%
“…To date, various evidence for significant effects on physical (Vitiello et al, 2013) and cognitive functions (Tomporowski, 2002; Cona et al, 2015; Hurdiel et al, 2015; Tonacci et al, 2016) of ultra-trailers has already been observed, mainly caused by a mix of high altitude exposure (Yan, 2014), environmental conditions (Lefferts et al, 2016; Taylor et al, 2016)—including cold, heat and hypoxia—muscular fatigue, dehydration (Cian et al, 2000), and sleep deprivation (Davis et al, 2014; Fullagar et al, 2015). …”
Section: Introductionmentioning
confidence: 99%